Integrating Generative AI in Hackathons: Opportunities, Challenges, and Educational Implications - Ramteja Sajja; Carlos Erazo Ramirez; Zhouyayan Li; Bekir Z. Demiray; Yusuf Sermet; Ibrahim Demir (Big Data and Cognitive Computing)
Hackathons have become essential in the software industry, fostering innovation and skill development for both organizations and students. These events facilitate rapid prototyping for companies while providing students with hands-on learning opportunities that bridge theory and practice. Over time, hackathons have evolved from competitive arenas into dynamic educational platforms, promoting collaboration between academia and industry. The integration of artificial intelligence (AI) and machine learning is transforming hackathons, enhancing learning experiences, and introducing ethical considerations. This study examines the impact of generative AI tools on technological decision-making during the 2023 University of Iowa Hackathon. It analyzes how AI influences project efficiency, learning outcomes, and collaboration, while addressing the ethical challenges posed by its use. The findings offer actionable insights and strategies for effectively integrating AI into future hackathons, balancing innovation, ethics, and educational value.